An Evidence Based Study of the Different Factors that Influence the Formation of Hammer Transfer Stains in a Crime Scene - Bandopadhyay, Samir Kumar; Basu, Nabanita (International Journal of Criminology and Sociology, 2014)
Weapon transfer stains in a crime scene are often difficult to interpret. Given the large number of hammer hit events that take place each year, this work is largely aimed at analyzing the different factors that influence and distort regular hammer transfer stains. Different physical mechanisms under identical conditions influence the formation of distinct transfer stain patterns. This is the basic highlight of this study. By experimentation, the authors are of the view that the quantity of blood attached to the surface area of a hammer, the surface area of the hammer exposed to blood, the dimensions of the hammer, the angle of inclination at the time of fall, hardness of the target surface, friction coefficient of the hammer material, texture of the target surface influence the transfer stain formed. Again the velocity of hit, the undulations in the hammer, the depth of blood pool, hammer weight all have significant effect on the transfer stain pattern formed. The significance of the height of fall and the edge that touches the target surface first, cannot be particularly ruled out in analyzing hammer transfer stain patterns. The relevance of the article lies in the fact that analysts having clear idea of how these different factors could affect the formation of different weapon transfer stain patterns, shall be in a better position at understanding the probable mechanism that might have led to the formation of the stain. This knowledge is transferable to the study of other murder weapon transfer stain interpretation and shall aid proper sequencing of segments in a criminal event.